Processing and Quality of Crystalized Palm Sugar in Indonesia: A Review - Hary Kurniawan; Sri Rahayoe; Hanim Zuhrotul Amnah (The University of Lampung, 2025)
Crystalized palm sugar derived from coconut and arenga palm sap has high-value for industrial products. The crystalized sugar offers several advantages over molded palm sugar, including a longer shelf life, lower glycemic index, and greater flexibility in its applications. However, palm sugar production in Indonesia is still predominantly carried out using traditional methods, which are inefficient in terms of quality control and production capacity. This review explores various aspects of palm sugar processing and quality in Indonesia, including raw materials, production processes, quality determinants, as well as challenges and development prospects. Key factors influencing product quality include the quality of raw materials, cooking techniques, drying methods, and proper storage practices. Uncontrolled fermentation of sap can hinder crystallization, while high moisture content may cause clumping and reduce product stability. To enhance global competitiveness, palm sugar must meet both the national and international certifications. The main challenges in this industry include the lack of Good Manufacturing Practices (GMP), limited adoption of modern processing technologies, and inconsistency in product quality. Quality improvement efforts through artisan training, production modernization, and supply chain strengthening are essential to ensuring that Indonesian palm sugar can compete in international markets. With proper strategies, palm sugar holds promising potential as a flagship export commodity from Indonesia.